Pelayanan Pendidikkan Pelatihan Seni dan Budaya Bagi Siswa/I SMP 3 Nagawutung Kecamatan Nagawutung Kabupaten Lembata - Marselina Kresensia Sulastri Min; Windhy Evelin Mathan; Marsela Indra; Rian Petrus Pati Matta; Bernardus Varnes Ogal; Innosensia E.I.Ndiki Satu; Marianus Kleden (Politeknik Kampar, 2024)
This work program is carried out with the aim of improving the skills and abilities of students at SMP 3 Nagawutung through arts and culture training. The method used in this activity is the Demonstration Method with the aim of finding out the skills and abilities of SMP 3 Nagawutung students directly. Arts training activities and this culture produces several works of art in the form of (traditional/cultural dances, poetry, speeches, vocal exercises and is performed at the 79th Independence Day of the Republic of Indonesia. The main targets in this activity are students of SMP 3 Nagawutung.